2016
DOI: 10.1039/c6tc04341k
|View full text |Cite
|
Sign up to set email alerts
|

Drastic solid-state luminescence color tuning of an archetypal Ir(iii) complex using polyoxometalates and its application as a vapoluminescence chemosensor

Abstract: New assemblies based on the archetypal [IrIII(ppy)2(bpy)]+ complex and a series of polyoxometalates exhibit highly tunable phosphorescence and vapoluminescence properties for detection of volatile organic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
7
17
0
Order By: Relevance
“…Interestingly, the emission wavelength of 1 + is only moderately modified between the diluted solution, the dilution in a PMMA matrix, and the condensed phase, which is commonly observed for AIE‐active heteroles . This singular optical feature contrasts with reported hybrid assemblies combining POMs and other luminescent molecules that often exhibit strong modulations of the emission energy . This is clearly an advantage in order to design new POM‐based emitters with better predictable emission wavelength.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…Interestingly, the emission wavelength of 1 + is only moderately modified between the diluted solution, the dilution in a PMMA matrix, and the condensed phase, which is commonly observed for AIE‐active heteroles . This singular optical feature contrasts with reported hybrid assemblies combining POMs and other luminescent molecules that often exhibit strong modulations of the emission energy . This is clearly an advantage in order to design new POM‐based emitters with better predictable emission wavelength.…”
Section: Methodsmentioning
confidence: 79%
“…Indeed, these non‐conventional redox and optically‐active metal‐oxide anions exhibit large sizes, high negative charges, and their nucleophilic oxygen surfaces are conducive to develop strong electrostatic and H‐bonding interactions with photoactive organic molecules, greatly impacting their photoactivity in the solid state . For instance, we recently used POMs as efficient structure‐directing agents to tune the photoresponses of photochromic spiropyrans and phosphorescent iridium complexes . Whereas molecular compounds based on POMs and non‐emissive tetraalkylphosphoniums have already been described, the unexplored ionic self‐assembly of AIE‐active phospholium derivatives with POMs through both anion‐π + and H‐bonding interactions appears as a promising strategy to develop new hybrid organic‐inorganic materials with improved solid‐state emission properties.…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that the electrostatic binding of POMs with [Ir III (ppy) 2 (bpy)] + can significantly alter the solid-state phosphorescence of the latter depending on the structural type of the formative POM and the framework of the resulting hybrids. In addition, the simple preparation procedure and the revealed vapoluminescence properties of these hybrids make them suitable candidates to serve as sensors for the selective detection of volatile organic compounds 47…”
Section: Pom-based Supramolecular Hybrid Compoundsmentioning
confidence: 99%
“…[25][26][27][28][29] Recently, ionic supramolecular assemblies have been easily built by mixing different polyoxoanions and a luminescent cationic cyclometalated Ir(III) complex. 30,31 Remarkably, the solid-state emission of the resulting compounds shifts from green to red depending on the nature of the POM and the crystal packing. Moreover, some of us recently designed novel supramolecular fluorescent materials by coupling POMs with an AIE-active phospholium, 32 and efficient solid-state emitters have been obtained by directing favorably the balance between AIE and ACQ effects using both anion-π + and H-bonding interactions.…”
Section: Introductionmentioning
confidence: 99%